Shared medical appointments for children and adolescents with type I diabetes: perspectives and experiences of patients, parents, and health care providers - Noordman J; Mejino A; van Dulmen S (Dove Medical Press, 2012)
Arlene Mejino,1 Janneke Noordman,1 Sandra van Dulmen1–31Netherlands Institute for Health Services Research (NIVEL), Utrecht, The Netherlands; 2Radboud University Nijmegen Medical Centre, Department of Primary and Community Care, Nijmegen, The Netherlands; 3Department of Health Science, Buskerud University College, Drammen, NorwayAims: This study examined the perspectives and experiences of patients, parents, and health care providers with shared medical appointments (SMAs) for children and adolescents with type 1 diabetes. Specifically studied were reasons to attend SMAs, perceived differences between SMAs and individual medical appointments, patient-valued health care aspects, and providers' performance.Methods: Fifty-two patients, 8 parents, and 36 health care providers participated. Perspectives on SMAs were assessed with questionnaires and an online focus group. Data was analyzed using descriptive statistics.Results: Health care providers had work-related reasons to conduct SMAs. Patients and parents primarily valued the presence of other patients during SMAs. According to health care providers and patients, a higher or similar amount of information was discussed during SMAs as opposed to individual appointments, respectively. SMAs did contain more discussion about lifestyle. Most consultation aspects considered important by the patients were performed by their health care providers. Patient satisfaction with SMAs did tend to decrease after 3 months. Parents were somewhat more critical about SMAs.Conclusions: Health care providers, patients, and parents were generally positive about SMAs. Future studies should examine the impact of the presence of parents and different health care providers during SMAs, and that of differences in patient age, type of insulin treatment, and disease-related problems.Keywords: child, adolescent, diabetes mellitus type 1, pediatrics, shared medical appointment